SIMULASI PERFORMA MOTOR ROKET BERTINGKAT - sri kliwati; Haris Setyawan; Wahyu Widada (Retii, 2019)
ABSTRACT This paper discusses the simulation of rocket motor performance for prediction of flight test result. Flying performance targets, such as range, altitude, speed can be predicted by simulation to predict flight test from static test results of rocket motors and for rocket motor design. Starting with Matlab software with the main data input power of rocket motor, output obtained in the form of flight test data (range, altitude, speed, and acceleration). The results of this software can be used for multi-stage motor, so it is useful to design a rocket motor in order to meet the range for satellite orbiter. Keyword : simulation, rocket, performance